Afforestation improves soil fertility in south-eastern Spain - Serrano, L Rojo; Jime, M N; Ferna, E; Ferna, J; Roca, A; Aguilar, J; Fernandez-Ondono, E; Rojo Serrano, L; Jiménez, M N; Navarro, F B; Diez, M; Martin, F; et al. (EUROPEAN JOURNAL OF FOREST RESEARCH, 2010)
In the 20th century, in the Mediterranean area, many extensive afforestation efforts were made with the primary objective of protecting soils from erosion and improving their fertility. This study evaluates the effects of the afforestation undertaken in the Guadalentin basin (SE Spain) with respect to the organic and inorganic soil constituents and physico-chemical soil properties. Given the phytoclimatic environments in the basin (sclerophyllous and hyperxerophyllous), paired samples were taken beneath the tree canopy of the pine plantations and in nearby open zones. With the same methodology, samples were taken from areas considered to be native forest. The data were submitted to different multivariate analyses of variance (two-way MANOVAs) in order to compare the effects and interactions of the factors CANOPY (with and without trees), PHYTOCLIMATE (sclerophyllous and hyperxerophyllous), and TYPE OF FOREST (afforested or native) on the dependent variables measured (soil variables). Significant differences were found at 0-10 cm in soil depth under pine afforestations in relation to adjacent open areas. Below this depth, differences were found only between phytoclimatic environments. No significant interactions were found between the variables analysed at any of the depths, indicating that the effects of the afforestations on the soil characteristics were independent of the phytoclimatic environment. The afforestation in the Guadalentin basin, in the two phytoclimatic environments considered increased the soil fertility. Nevertheless, the native forests presented the highest soil organic-carbon contents, mainly in the sclerophyllous phytoclimate type (Quercus ilex subsp. ballota forests). Therefore, although the afforestations improved the soil fertility in relation to the open areas, the maximum potential has probably not been reached in relation to that observed in the native forests. The effects that forest development (age, basal area) over time exerts on soil properties remain to be verified by further research.
Keywords: Afforestation; Differential pedological characteristics; Guadalentin basin; organic carbon

Estimation of the organic carbon stock in the ecosystem of the Middle Atlas Moroccan Quercus ilex forest - Boulmane, Mohamed; Makhloufi, Mohamed; Bouillet, Jean-Pierre; Saint-Andre, Laurent; Satrani, Badr; Halim, Mohamed; Elantry-Tazi, Salwa (ACTA BOTANICA GALLICA, 2010)
The present study was carried out in Quercus ilex forest of the Middle Moroccan Central Atlas (Tafachna and Reggada). It aims at the determination of the organic carbon stock in the various layers of the soils, the litter and the various components of the tree (wood of the trunk, bark, branches, smal branches and leaves). It comes out from this study that the stock of total carbon (SCOT) in the ecosystem of the holm oak is of 145 t C/ha for Tafachna and 114 t C/ha for Reggada. The organic carbon stock of soils (SCOS) represents more than 50% of the SCT. This stock varies considerably with the density of peuplement with 80 t C/ha for Tafachna (5192 species/ha) and 56 t C/ha for Reggada (1584 species/ha). Contrary to the carbon stock in the phytomass which is equal 64 t C/ha for Tafachna and 58 t C/ha for Reggada. More than 80% of the organic carbon stock of the soils is stored in the first 30 centimeters, that is about 63 t/ha (43% of the SCOT) for Tafachna and 47 t/ha (41% of the SCOT) for Reggada.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: biomass; mineralisation; organic carbon; Soil

Exchange Complex Composition in Mediterranean Ultisols Under Various Types of Vegetation and Soil Uses - Mariscal-Sancho, Ignacio; Peregrina, Fernando; Mendiola, Maria A; Santano, Jesus; Espejo, Rafael (SOIL SCIENCE, 2009)
We studied the dynamics of texture, bulk density, exchangeable bases, acidity, and aluminum in the uppermost Surface 50 con of Mediterranean Ultisols under natural vegetation at variable degradation stages and tinder different soil uses in the Canamero's rana formation (southwest Spain). The areas studied included a cork oak grove (the climax vegetation in the area), a field densely covered by Cistus ladaniferus L., a field with 55% covered by Cistus crispus L. and C. ladaniferus, a field with 10% covered by bushes of the same type as the previous one, and a field with grass and occasional Cistus bushes. All of these fields with bushes were extensively cultivated with rye (Secale. cereale L.) and then abandoned 45, 35, 12, and 6 years, respectively, before the study. Finally, we selected an olive grove that had been under continuous tillage for the previous 65 years. The total organic matter content decreased, starting from the virgin soil, under cork oaks, to the most heavily degraded soil (that under olive trees), whereas the bulk density increased. The total contents of exchangeable Ca, Mg, Na, and K significantly decreased in the same trend as organic matter. In contrast, the amount of aluminum extracted by 1N KCl, Al(K), remained essentially constant or even increased with increasing soil degradation. This resulted in a markedly decreased Ca/Al(K) ratio in the topmost 5 cm of soil, which had a strong adverse effect on crop productivity and natural plant recovery after the soils were abandoned.
Keywords: organic carbon; Soil degradation; soil quality; storage bases

Exchange Complex Composition in Mediterranean Ultisols Under Various Types of Vegetation and Soil Uses - Mariscal-Sancho, Ignacio; Peregrina, Fernando; Mendiola, Maria A.; Santano, Jesus; Espejo, Rafael (SOIL SCIENCE, 2009)
We studied the dynamics of texture, bulk density, exchangeable bases, acidity, and aluminum in the uppermost Surface 50 con of Mediterranean Ultisols under natural vegetation at variable degradation stages and tinder different soil uses in the Canamero's rana formation (southwest Spain). The areas studied included a cork oak grove (the climax vegetation in the area), a field densely covered by Cistus ladaniferus L., a field with 55% covered by Cistus crispus L. and C. ladaniferus, a field with 10% covered by bushes of the same type as the previous one, and a field with grass and occasional Cistus bushes. All of these fields with bushes were extensively cultivated with rye (Secale. cereale L.) and then abandoned 45, 35, 12, and 6 years, respectively, before the study. Finally, we selected an olive grove that had been under continuous tillage for the previous 65 years. The total organic matter content decreased, starting from the virgin soil, under cork oaks, to the most heavily degraded soil (that under olive trees), whereas the bulk density increased. The total contents of exchangeable Ca, Mg, Na, and K significantly decreased in the same trend as organic matter. In contrast, the amount of aluminum extracted by 1N KCl, Al(K), remained essentially constant or even increased with increasing soil degradation. This resulted in a markedly decreased Ca/Al(K) ratio in the topmost 5 cm of soil, which had a strong adverse effect on crop productivity and natural plant recovery after the soils were abandoned.
The following values have no corresponding Zotero field: pub-location: 530 WALNUT ST, PHILADELPHIA, PA 19106-3621 USA publisher: LIPPINCOTT WILLIAMS & WILKINS
Keywords: organic carbon; Soil degradation; soil quality; storage bases